The Performative Turn in Poetry: Theoretical Perspectives and New Languages - González Gil, Isabel (Tropelías: Review of Literary Theory and Comparative Literature, 2023)
Performativity has become one of the main categories for understanding contemporary literature, including poetic languages. However, theoretical contributions in this regard come from diverse and not always reconcilable fields. Performance theories such as those by Schechner (1977), Phelan (1993), and Fischer-Lichte (2004) allow us to approach poetic practices that emerge in hybrid territories between poetry, the stage, avant-garde art, and technological neo-orality, for instance perfopoetry, sound poetry, poetic actions, and slam poetry. These practices share certain features, particularly the importance of event over representation, the semiotic inscription of the body, co-presence, and a return to the community. On the other hand, theories of the lyric, such as that of Jonathan Culler (2015), have drawn attention to the performative aspects of the poem (repetition, rhythm, meter, rhyme, etc.). This article explores these theoretical contributions along three axes, namely performance poetry,theories on the performance of the poem, and the construction of authorial postures and identities, examining which codes are specific to lyric genre and the extent to which we can speak of a "performative turn" in poetry.
Keywords: performativity; performance; lyric theory; perfopoetry; contemporary spanish poetry